Battery Energy Storage System (BESS) as a voltage control at substation based on the defense scheme mechanism - Arifin, Zainal; Firmanto, Aditya; Dwirawan, Sirilus; Alwani, Dede Rilwan (SINERGI, 2024)
Battery Energy Storage Systems (BESS) can improve power quality in a grid with various integrated energy resources. The BESS can adjust the supply and demand to maintain a more stable, reliable, and resilient power system. Connected to the grid, BESS can respond quickly as a voltage regulator on the grid in the event of a voltage drop during peak load or when a disturbance occurs. Thus, the equipment has designed a voltage regulation scheme to prevent voltage drops and poor power quality caused by some rapid voltage fluctuations. This study investigates the role of BESS as a voltage control combined with a defense scheme mechanism at a high-voltage network in Jakarta. ETAP modeling software has investigated several voltage regulation systems with BESS at the substation indications. The results showed that the BESS at Substations can improve the voltage quality on the grid through voltage regulation.